Damage development in glass-fibre-reinforced polymers (GFRP)under transverse loading - Kuboki, T; Jar, P.Y.B.; Cheng, J.J.R.
Objectives of the work are to use optical microscopy to identify matrix cracks that lead to delamination in cross-ply glass-fibre-reinforced polymers (GFRP)under transverse loading and to provide evidence on the associated damage evolvement procedure. Sequence of the damage evolvement was established by examining a series of identical specimens that had been subjected to different levels of loading. The results were found to be consistent with those reported in the literature, that the transverse loading generated both bending and shear cracks in the matrix, and that it was the shear cracks that initiate the delamination. What was revealed in the current study is that delamination in the bottom half of the cross section, i.e. away from the contact surface, developed first, from shear cracks in regions of mid-thickness. Only after the load was further increased was delamination in the top half of the cross-section developed, from cracks generated by stress concentration around the contact area. The study also showed that the matrix shear cracking can 'cut through' the fibre bundle in the lamina of the central region, for further growth of the shear cracks or development of delamination towards the back surface. On some occasions, growth of the shear cracks appears to be continuous under the microscopic observation, not interrupted by the cross-ply fibre lay-up.
Keywords: GFRP; TRANSVERSE LOADING; MATRIX CRACKING; DELAMINATIONS; INDENTATION